California Democratic Council Statewide Convention at Hacienda Inn - Watkins, Howard::::::::: (1982)
head table with Lia Triff Belli, U.S. Senator Ted Kennedy, ???, CDC President Wally Albertson "Convention Banner: "We the people action for the '90's"